Land Rights Dispute Resolution Through Mediation Process With Involving Third Parties For Buyers (Case Study In Blora District Land Office) - Indra Kurniawan; Umar Ma’ruf (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to: 1) To analyze the role of a third party as a buyer in the resolution of land disputes in the District Land Office Blora 2).To analyze constraints and solutions in the settlement of land disputes by mediation in Blora District Land Office.The research method approach used by the authors is empirical juridical approach. Specifications research using analytical descriptive. The data used is data qualitative, while the data collection techniques used were interviews and literature.From the research we concluded that 1) A third party that acts as a creditor with good intention to buy the land on which the object is helpful in resolving issues of conflict between the parties, so that the conflict can be resolved without going through the litigation. 2) Obstacles encountered in the process of mediation in Blora district land office the address of domicile of the parties is less clear, the willingness of the parties to attend mediation, the emotions of the Parties and the willingness of the Parties to resolve the conflict by peaceful means. Notice mediation may be submitted to the village chief residence of the parties. Mediators should create an atmosphere of calm, relaxed but focused on the purpose of mediation.Keywords: Mediation; The parties; Barriers; Solutions